Community-Based Family Education and Assistance for Improved Nutrition - Andi Mukarramah; Lestari Lorna Lolo; Nancy Sylvia Bawiling; Suprapto (Abdimas Polsaka, 2026)
Malnutrition remains a major public health problem, particularly in communities where families have limited access to nutrition information and health services. Family knowledge and daily dietary practices play a crucial role in determining nutritional status, especially among children and vulnerable household members. This community service program aimed to improve family nutrition through community-based education and assistance implemented at a primary healthcare center in Makassar, Indonesia. The program involved 30 family respondents and used a structured five-stage approach: preparation, baseline assessment, nutrition education, family assistance and mentoring, and monitoring and evaluation. Educational activities focused on balanced nutrition, local food utilization, family meal planning, and food hygiene, supported by practical demonstrations and continuous mentoring. The program's effectiveness was evaluated using pre- and post-test assessments of nutrition knowledge, balanced diet practices, and food hygiene awareness. The results showed consistent improvements across all indicators after the intervention, indicating enhanced understanding and adoption of healthy nutritional behaviors at the household level. These findings demonstrate that integrating structured nutrition education with hands-on assistance can effectively translate knowledge into practice. Overall, the program highlights the importance of family-centered and participatory approaches in addressing community nutrition problems. Community-based family education and assistance represent a feasible and sustainable strategy to strengthen family capacity, promote healthy dietary behaviors, and support nutrition improvement within primary healthcare settings